Identifikasi Kebutuhan Masyarakat terhadap Pendirian Taman Bacaan Masyarakat di Desa Tanjung Seteko Kecamatan Indralaya - Candra, Adi; Husin, Azizah (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2018)
The identification of community needs has been undertaken to describe what needs are needed by the community in establishing a community reading park in TanjungSeteko Village, Indralaya Sub-district. Identification is done by using the Community Learning Needs Card System (SKBM) and survey. Data were collected through questionnaires and documentation. The research results show that the learning needs of the people of TanjungSeteko village are the learning needs of religious, economic, literacy and nationality, sports, health and environment. Community learning needs illustrate the need for community empowerment programs supported by human resources (managers), sources of information in the form of books, places of study, and funding. Thus community empowerment programs through the establishment of community reading parks can meet community learning needs.